A high-salt-resistant n-s co-doped amino-modified hierarchical porous carbon adsorption material and preparation and application thereof

CN122912808APending Publication Date: 2026-10-16XIAN HENGXU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611390867.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0009]本发明的目的在于提供一种耐高盐N-S共掺杂氨基改性多级孔碳吸附材料及其制备和应用,以克服现有技术存在的如下技术缺陷:传统多孔碳材料、吸附树脂等依赖静电吸附机制、范德华力,在煤化工、石化、湿法冶金等高盐母液、釜残液复杂体系中,受大量共存阴阳离子、钙镁及金属离子干扰,双电层压缩、活性位点被竞争占据,吸附容量显著下降;普通无序碳材料孔道连通性差,高盐体系中钙镁盐、硅酸盐、磷酸盐易结晶结垢堵塞,同时腐殖质、合成高分子大分子、非离子表面活性剂易堵塞、包裹吸附位点,传质阻力大、材料使用寿命短;单一杂原子改性材料活性位点类型单一,对联苯、多氯联苯、杂环芳烃、腐殖质、合成高分子类大分子难降解有机污染物吸附能力不足;常规氧化改性碳材料含有大量静电型官能团,高盐多离子共存环境易发生离子交换失活;传统活性炭吸附材料多采用高温热再生工艺,易造成杂原子位点烧蚀、表面官能团分解、碳骨架坍塌,材料损耗大、循环性能差

Benefits of technology

1、有序介孔-微孔多级孔结构:有序介孔构建大流量传质通道,降低高盐复杂体系有机物扩散阻力,缓解钙镁盐、硅酸盐、磷酸盐结晶堵孔,同时为腐殖质、合成高分子类大分子有机物提供扩散通道,避免微孔快速堵塞;均匀微孔形成限域吸附空腔,富集小分子难降解有机物,提升对杂环芳烃、联苯、多氯联苯污染物的吸附容量与活性位点利用率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912808A_ABST
    Figure CN122912808A_ABST
Patent Text Reader

Abstract

The application discloses a high-salt-resistant N-S co-doped amino-modified multi-level porous carbon adsorption material and a preparation and application thereof. A substrate of the adsorption material is an ordered mesoporous-microporous multi-level porous carbon prepared by a soft template method. Nitrogen and sulfur double heteroatoms are in-situ co-doped in a carbon skeleton of the ordered mesoporous-microporous multi-level porous carbon, and skeleton active sites include pyridine nitrogen, graphite nitrogen and thiophene sulfur. Primary amino functional groups are uniformly grafted on an outer surface and a pore channel inner surface of the ordered mesoporous-microporous carbon through silane covalent bonds. The adsorption material takes a non-electrostatic adsorption mechanism as a core adsorption path, and the non-electrostatic adsorption mechanism is a pi-pi stacking interaction, a halogen bond interaction, an S-X affinity interaction and an N-H...X hydrogen bond. The application avoids micropore rapid clogging, improves adsorption capacity and active site utilization rate of heterocyclic aromatic hydrocarbons, biphenyl and polychlorinated biphenyl pollutants, improves adsorption capacity of non-ionic surfactants and humus, avoids ion exchange inactivation under a high-salt multi-ion coexistence condition, reduces rigid attachment of macromolecular organic matters, and is suitable for a high-salt working condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmentally friendly functional adsorption materials and their industrial wastewater treatment technology. Specifically, it relates to a high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorption material, and also relates to its preparation method and application. It is particularly suitable for high-salt wastewater such as membrane concentrate, evaporation crystallization mother liquor, and reactor residue in the chemical industry, and can adsorb and remove aromatic compounds, halogenated hydrocarbons, heterocyclic aromatic hydrocarbons, biphenyls, polychlorinated biphenyls, nonionic surfactants, humic substances, and synthetic polymers that are difficult to degrade. Background Technology

[0002] The production processes of coal chemical, petrochemical, hydrometallurgical, pesticide, pharmaceutical, and fine chemical industries generate large amounts of high-salt wastewater, such as membrane concentrate, evaporation crystallization mother liquor, and reactor residue. The total salt content of this type of wastewater reaches over 20%, with sodium sulfate and sodium chloride being the main salt components, accounting for 80-90%, or even over 90%, of the total salt. The wastewater contains hydrophobic and recalcitrant organic compounds such as halogenated hydrocarbons, aromatics, heterocyclic aromatics, biphenyls, and polychlorinated biphenyls, as well as nonionic surfactants, humic substances, and synthetic polymers that are soluble and recalcitrant organic pollutants. The organic pollutants are complex and have extremely poor biodegradability. Simultaneously, the system contains various inorganic impurities, including fluoride ions, potassium ions, calcium ions, magnesium ions, free silicon, carbonate ions, bicarbonate ions, nitrate ions, nitrite ions, phosphate ions, iron ions, aluminum ions, manganese ions, and heavy metals. Among these, calcium and magnesium ions readily combine with carbonate, phosphate, and silicate ions in the system to form precipitates, easily causing scaling and blockage of the adsorption material pores. If the aforementioned complex and recalcitrant organic pollutants are not removed in advance, they will significantly reduce the quality of subsequent evaporated crystallized salt products, increase the scaling rate of the system, increase the amount of hazardous waste generated and the overall wastewater treatment cost, and restrict the stable operation of the zero-discharge process for high-salt wastewater.

[0003] Traditional activated carbon, ordinary porous carbon, and adsorption resins primarily rely on hydrophobic interactions, electrostatic adsorption, and van der Waals forces to remove organic matter. However, in the aforementioned high-salinity and complex water bodies, a large number of anions and cations, as well as sodium, calcium, and magnesium ions, compress the water's electrical double layer, competing for adsorption active sites. Simultaneously, components such as calcium and magnesium ions, free silicon, carbonates, and phosphates easily precipitate and form scale within the pores. Furthermore, large molecular organic matter such as humic substances and synthetic polymers easily clog the material's microporous channels, and nonionic surfactants readily form a coating layer on the material surface. These factors further lead to a significant decrease in adsorption capacity, loss of adsorption selectivity, and pore blockage, resulting in highly unstable treatment performance that fails to meet the engineering requirements for pretreatment of membrane concentrates, mother liquors, and reactor residues.

[0004] Regarding the modification of carbon-based adsorbent materials, existing technologies have disclosed various improvement schemes. Patent CN100469692C discloses a nitrogen-containing ordered mesoporous carbon and its synthesis method. This method uses soluble resin and nonionic surfactants such as F127 to induce self-assembly of ordered mesoporous carbon via solvent evaporation. The carbon has a pore size of 2.0–6.0 nm, a specific surface area of ​​500–1200 m² / g, and a carbon-nitrogen molar ratio of 100:0.20–100:10.00. Its application in the adsorption of phenol-containing wastewater is also disclosed. While this scheme constructs an ordered mesoporous structure and introduces nitrogen into the carbon framework, the pores are predominantly mesoporous, lacking a hierarchical multi-level pore structure with interconnected micropores and mesopores. It only performs single nitrogen doping without introducing sulfur heteroatoms and amino functional groups, resulting in a limited variety of adsorption active sites. This makes it difficult to meet the synergistic removal requirements of multiple types of recalcitrant organic matter in complex, high-salt wastewater.

[0005] Publication No. CN113893821A discloses a nitrogen-sulfur-doped porous carbon material noble metal adsorbent for adsorbing and recovering precious metals such as gold. Although the above-mentioned nitrogen-sulfur co-doped carbon materials can control the surface chemical properties of carbon materials through heteroatom doping, they all have limitations: they are either disordered microporous biomass carbon, lacking ordered mesoporous-microporous interconnected mass transfer and anti-clogging structures, or they are used for catalytic oxidation degradation, precious metal recovery and other scenarios rather than selective adsorption of organic pollutants in high-salt wastewater. Moreover, none of them involve covalent grafting of amino functional groups, and they have not been systematically designed to meet the anti-interference and anti-scaling requirements of high-salt multi-impurity coexisting systems.

[0006] In the field of amino-functionalized adsorbent materials, existing research enhances adsorption by grafting amino groups onto the surface of mesoporous materials and leveraging the hydrogen bonding between amino groups and organic pollutants. Examples include the adsorption study of 1,2-dichloroethane in water by amino-modified MCM-41 reported in *Environmental Chemistry* in 2022, and the broad-spectrum adsorption of organic pollutants by amino-functionalized activated carbon / graphene aerogels in existing technologies. However, these approaches are mostly based on single amino functionalization without synergistic effects from nitrogen and sulfur co-doping of the carbon framework. Their adsorption capacity for highly hydrophobic biphenyls, polychlorinated biphenyls, humic substances, synthetic polymers, and other large, recalcitrant organic molecules is limited, and their adaptability to high-salt conditions is insufficient.

[0007] In summary, existing modified carbon materials generally employ single nitrogen doping, single sulfur doping, oxidative modification, or simple surface amino modification techniques, which have many inherent technical defects: single nitrogen doping materials have weak adsorption capacity for polar halogenated and surfactant pollutants; single sulfur doping materials have insufficient π-π adsorption capacity for aromatic, heterocyclic aromatic hydrocarbons, and humic macromolecules; the carboxyl and sulfonic acid groups introduced by oxidative modification are highly electrostatically active sites, which are prone to cation exchange and rapid failure in high-salt, multi-ion coexistence environments; at the same time, traditional modified carbon materials are mostly disordered porous structures with chaotic pores and poor connectivity. Under high-salt mother liquor conditions, calcium and magnesium salts, silicates, and phosphates are prone to crystallization and pore blockage, which, combined with the pore blockage problem of polymers and humic macromolecules, results in high mass transfer resistance and poor cycle stability.

[0008] The existing technology has not yet disclosed a complete integrated technical solution for "precise construction of ordered mesoporous-microporous hierarchical pore structure with soft template, N-S in-situ co-doping of carbon skeleton, amino covalent grafting throughout the pores, and low-temperature regeneration process adapted to high-salt wastewater conditions". It lacks a fully non-electrostatic synergistic adsorption system that is specifically adapted to high-salt, multi-impurity, multi-type recalcitrant organic matter coexisting environment and can efficiently and simultaneously remove halogenated hydrocarbons, heterocyclic aromatic hydrocarbons, biphenyls, polychlorinated biphenyls, nonionic surfactants, humic substances, and synthetic polymer pollutants. It is difficult to simultaneously meet the industrial application requirements of high-salt anti-interference, anti-scaling interference of multiple inorganic impurities such as calcium and magnesium, selective removal of multiple types of recalcitrant organic pollutants, structural stability, and recyclability. Summary of the Invention

[0009] The purpose of this invention is to provide a high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent material, its preparation, and its application, to overcome the following technical defects in the prior art: Traditional porous carbon materials and adsorption resins rely on electrostatic adsorption mechanisms and van der Waals forces. In complex systems of high-salt mother liquor and reactor residues in coal chemical, petrochemical, and hydrometallurgical processes, they are subject to interference from a large number of coexisting anions and cations, calcium and magnesium ions, and metal ions, resulting in double-layer compression, competitive occupation of active sites, and a significant decrease in adsorption capacity; Ordinary disordered carbon materials have poor pore connectivity, and calcium and magnesium salts, silicates, and phosphates in high-salt systems are prone to crystallization, scaling, and blockage, while also causing humification. Polymers, synthetic macromolecules, and nonionic surfactants easily clog and encapsulate adsorption sites, resulting in high mass transfer resistance and short material lifespan. Single heteroatom modified materials have limited active site types and insufficient adsorption capacity for biphenyls, polychlorinated biphenyls, heterocyclic aromatic hydrocarbons, humic substances, and recalcitrant organic pollutants such as synthetic macromolecules. Conventional oxidative modified carbon materials contain a large number of electrostatic functional groups, which easily lead to ion exchange deactivation in high-salt, multi-ion environments. Traditional activated carbon adsorption materials often employ high-temperature thermal regeneration processes, which easily cause heteroatom site ablation, surface functional group decomposition, and carbon skeleton collapse, resulting in high material loss and poor cycle performance.

[0010] The objective of this invention is achieved as follows: a high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material, characterized in that the matrix of the adsorbent material is an ordered mesoporous-microporous hierarchical porous carbon prepared by a soft template method; the carbon framework of this ordered mesoporous-microporous hierarchical porous carbon is in-situ co-doped with nitrogen and sulfur dual heteroatoms, and the active sites of the framework include pyridine nitrogen, graphitic nitrogen, and thiophene sulfur; primary amino functional groups are uniformly grafted onto the outer surface and inner surface of the pores of the ordered mesoporous-microporous carbon via silane covalent bonds. The adsorbent material uses non-electrostatic adsorption mechanisms such as π-π stacking interactions, halogen bonding, S-X affinity, and N-H…X hydrogen bonding as its core adsorption pathways, and is not affected by competition from multiple coexisting ions in high-salt systems.

[0011] In one embodiment, the ordered mesoporous-microporous hierarchical carbon has an ordered mesoporous pore size of 2-6 nm, a microporous pore size of 0.4-0.8 nm, and a BET specific surface area of ​​1200-1800 m² / g; the total nitrogen doping content in the carbon framework is 4.0-8.0 at.%, wherein the total proportion of pyridine nitrogen and graphitic nitrogen is not less than 75% of the total nitrogen content; the sulfur element in the carbon framework is mainly in the form of thiophene sulfur C-S-C, and the molar proportion of oxidized sulfur species is less than 15%; the content of primary amine functional groups covalently grafted on the surface of the carbon material is 1.8-3.2 at.%.

[0012] A method for preparing a high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent material includes the following steps: (1) Preparation of ordered mesoporous-microporous hierarchical carbon matrix by soft template method: F127 was used as mesoporous soft template agent, resorcinol-formaldehyde resin was used as carbon source, ethanol and deionized water were used as mixed solvent as dispersion system, and ammonia was used as alkaline catalyst. After solvent evaporation-induced self-assembly, isothermal curing, high temperature carbonization and template removal, ordered mesoporous-microporous hierarchical carbon matrix was obtained. (2) N-S dual heteroatom co-doping modification: The ordered mesoporous-microporous hierarchical carbon matrix prepared in step (1) is uniformly mixed and ground with thiourea solid dopant, and then pyrolyzed at high temperature under nitrogen inert atmosphere to generate pyridine nitrogen, graphitic nitrogen and thiophene sulfur active sites in situ inside the carbon skeleton to obtain N-S co-doped ordered mesoporous-microporous carbon. (3) Secondary amino covalent grafting modification: The N-S co-doped ordered mesoporous-microporous carbon obtained in step (2) is surface activated, placed in a mixed solvent system of ethanol and water, and the coupling agent aminopropyltriethoxysilane is added for liquid phase reflux reaction. Primary amino functional groups are covalently grafted on the outer surface and inner surface of the pores of the carbon material. After washing and drying, high salt resistant N-S co-doped amino modified hierarchical porous carbon adsorbent material is obtained.

[0013] In one embodiment, the mass ratio of each raw material in step (1) is as follows: F127: resorcinol: 37% formaldehyde solution: ethanol: deionized water: 25%~28% ammonia = 1.0: 1.0~1.4: 1.4~1.8: 22~28: 8~12: 0.2~0.4; the solvent evaporation-induced self-assembly temperature is 35~45℃, and the evaporation time is 18~26h; the curing temperature is 85~105℃, and the curing time is 12~20h; the carbonization temperature is 500~600℃, and the heat preservation time is 2~3h, with nitrogen protection throughout the process.

[0014] In one embodiment, the mass ratio of ordered mesoporous-microporous hierarchical carbon to thiourea dopant in step (2) is 1:2 to 4; the pyrolysis calcination temperature is 700 to 900°C, the holding time is 2 to 4 hours, the heating rate is 5 to 10°C / min, and the entire process is carried out in a nitrogen inert atmosphere.

[0015] In one embodiment, the mass ratio of ethanol to water in the ethanol-water mixed solvent system described in step (3) is 3 to 5:1; the total mass fraction of aminopropyltriethoxysilane in the liquid phase system is 2% to 5%; the reflux temperature is 60 to 80°C, and the reflux reaction time is 4 to 8 hours.

[0016] An application of a high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material is disclosed, which is used to treat high-salt wastewater generated in the coal chemical, petrochemical, hydrometallurgical, pesticide, pharmaceutical, and fine chemical industries. The high-salt wastewater includes membrane concentrate, evaporation crystallization mother liquor, and reactor residue.

[0017] In one embodiment, the total salt content of the high-salt wastewater is more than 20%, and the main salts are sodium chloride and sodium sulfate, with sodium chloride and sodium sulfate accounting for 80-90% of the total salt. The wastewater contains fluoride ions, potassium ions, calcium ions, magnesium ions, free silicon, carbonate ions, bicarbonate ions, nitrate ions, nitrite ions, phosphate ions, as well as iron, aluminum, manganese and heavy metal impurities.

[0018] In one embodiment, the pH of the high-salinity wastewater is controlled between 7.0 and 10.0 during treatment, and the adsorbent material is used to selectively adsorb aromatic compounds, halogenated hydrocarbons, heterocyclic aromatic hydrocarbons, biphenyls, polychlorinated biphenyls, nonionic surfactants, humic substances, and synthetic polymeric recalcitrant organic pollutants in the wastewater.

[0019] In one embodiment, the adsorbent material after adsorption saturation is regenerated and reused. The regeneration method is as follows: first, the adsorbent material is thoroughly rinsed with deionized water, and then it is heated at 100-130°C for 2-4 hours under normal pressure air or an inert atmosphere for low-temperature thermal desorption regeneration. After cooling, it is used again for adsorption of organic pollutants in high-salt wastewater.

[0020] The beneficial effects of this invention are as follows: 1. Ordered mesoporous-microporous hierarchical structure: Ordered mesopores construct high-flow-rate mass transfer channels, reduce the diffusion resistance of organic matter in high-salt complex systems, alleviate the blockage of pores by calcium and magnesium salts, silicates, and phosphates, and at the same time provide diffusion channels for humic substances and synthetic macromolecular organic matter, avoiding rapid blockage of micropores; Uniform micropores form confined adsorption cavities, enrich small molecule recalcitrant organic matter, and improve the adsorption capacity and active site utilization of heterocyclic aromatic hydrocarbons, biphenyls, and polychlorinated biphenyls pollutants.

[0021] 2. N-S framework co-doping system: Pyridine nitrogen and graphitic nitrogen provide π-π stacking and halogen bond interaction, which is suitable for aromatic, heterocyclic aromatic hydrocarbons, halogenated hydrocarbons, biphenyls, and polychlorinated biphenyls pollutants. At the same time, they enhance the hydrophobicity of the material surface and improve the adsorption capacity for nonionic surfactants and humic substances. Thiophene sulfur provides S-X specific affinity interaction and strengthens the adsorption stability of halogenated organic compounds. By controlling the proportion of oxidized sulfur, ion exchange deactivation under high salt and multi-ion coexistence conditions can be avoided.

[0022] 3. Covalent grafting of amino groups throughout the pores: Primary amino groups are uniformly grafted onto the inner and outer surfaces of carbon materials to construct an N-H…X hydrogen bond-halogen bond synergistic adsorption system, which enhances the adsorption capacity of polar halogenated and surfactant pollutants, while improving the surface wettability of the material and reducing the rigid adhesion of macromolecular organic matter.

[0023] 4. Non-electrostatic adsorption mechanism: The adsorption process relies on multiple non-electrostatic interactions such as π-π interaction, halogen bond, S-X affinity, and hydrogen bond, which completely avoids the negative impact of competitive adsorption and double layer compression of a large number of coexisting anions, cations, calcium and magnesium ions, and metal ions, and is suitable for high-salt and complex working conditions.

[0024] 5. Mild regeneration system: It adopts a combination process of first washing with water to remove salt and impurities, and then low-temperature thermal desorption. Water washing can effectively wash away salt scale in the pores, nonionic surfactants and macromolecular organic debris on the surface, and low-temperature thermal desorption thoroughly decomposes various adsorbed organic substances, while avoiding functional group ablation and framework collapse caused by high temperature, which greatly improves the cycle stability of the material under complex high-salt mother liquor conditions. Detailed Implementation

[0025] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.

[0026] Example 1: A method for preparing a high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material, comprising the following steps: (1) Preparation of ordered mesoporous-microporous hierarchical porous carbon matrix by soft template method: Weigh each raw material according to the mass ratio of F127:resorcinol:37% formaldehyde solution:ethanol:deionized water:25%~28% ammonia water = 1.0:1.2:1.6:25:10:0.3; completely dissolve F127 in the ethanol-water mixed solvent, add ammonia water and stir evenly, add resorcinol and dissolve thoroughly, then slowly add formaldehyde solution dropwise, stir at room temperature for 40 min; spread the mixture evenly in a petri dish, allow the solvent to evaporate at 40℃ for self-assembly for 22 h, and cure at 95℃ for 16 h to obtain the resin precursor; place the precursor in a tube furnace, hold at 550℃ in a nitrogen atmosphere for 2.5 h for carbonization to remove the template, and allow to cool naturally to obtain an ordered mesoporous-microporous hierarchical porous carbon matrix; (2) N-S dual heteroatom co-doping modification: Take 1g of the above ordered mesoporous-microporous carbon and 3g of thiourea, grind and mix thoroughly, calcine in a tube furnace at 800℃ for 3h under nitrogen atmosphere, heating rate 8℃ / min, and cool naturally to obtain N-S co-doped ordered mesoporous-microporous carbon. (3) Secondary amino covalent grafting modification: A mixed solvent of ethanol and water in a mass ratio of 4:1 was prepared, and 3% (w / w) of aminopropyltriethoxysilane was added to disperse 0.5 g of N-S co-doped carbon. The mixture was refluxed at 70 °C for 6 h. After the reaction was completed, the mixture was washed with ethanol and deionized water until neutral, and then dried at 60 °C to obtain a high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent.

[0027] Key parameters of the material prepared in this embodiment: BET specific surface area 1520 m² / g, mesopore diameter 3.8 nm, micropore diameter 0.62 nm; nitrogen doping amount 6.3 at.%, with pyridine nitrogen + graphitic nitrogen accounting for 82.5%; sulfur doping amount 5.1 at.%, with thiophene sulfur accounting for 87.2% and oxidized sulfur accounting for 12.8%; amino grafting amount 2.5 at.

[0028] High salt adsorption performance: Simulated coal chemical evaporation mother liquor system, total salt 22wt%, NaCl and The system contains 90% salt, and coexists with impurities such as fluoride, potassium, calcium, magnesium, phosphate, iron, and aluminum. The pollutants are a mixture of toluene, chlorobenzene, thiophene, biphenyl, nonionic surfactants, and humic substances. The saturated adsorption capacity of the mixed organic matter in this embodiment is 57.9 mg-TOC / g. After 15 cycles of regeneration, the adsorption capacity retention rate is 96.7%.

[0029] Example 2: A method for preparing a high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material, comprising the following steps: (1) Preparation of ordered mesoporous-microporous hierarchical porous carbon matrix by soft template method: Weigh each raw material according to the mass ratio of F127:resorcinol:37% formaldehyde solution:ethanol:deionized water:25%~28% ammonia water =1.0:1.0:1.4:22:8:0.2; completely dissolve F127 in the ethanol-water mixed solvent, add ammonia water and stir evenly, add resorcinol and dissolve it completely, then slowly add formaldehyde solution dropwise, stir at room temperature for 40 min; spread the mixture on a petri dish, self-assemble at 35℃ for 26 h for solvent evaporation, and cure at 85℃ for 20 h to obtain the resin precursor; place the precursor in a tube furnace, carbonize and remove the template at 500℃ for 3 h in a nitrogen atmosphere, and naturally cool to obtain an ordered mesoporous-microporous hierarchical porous carbon matrix; (2) N-S dual heteroatom co-doping modification: Take 1g of the above ordered mesoporous-microporous carbon and 2g of thiourea, grind and mix thoroughly, calcine in a tube furnace at 700℃ for 4h under nitrogen atmosphere, with a heating rate of 5℃ / min, and cool naturally to obtain N-S co-doped ordered mesoporous-microporous carbon. (3) Secondary amino covalent grafting modification: A mixed solvent of ethanol and water in a mass ratio of 3:1 was prepared, and 2% (w / w) of aminopropyltriethoxysilane was added to disperse 0.5 g of N-S co-doped carbon. The mixture was refluxed at 60 °C for 8 h. After the reaction was completed, the mixture was washed with ethanol and deionized water until neutral, and then dried at 60 °C to obtain a high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent.

[0030] Key parameters of the material prepared in this embodiment: BET specific surface area 1280 m² / g, mesopore diameter 2.5 nm, micropore diameter 0.45 nm; nitrogen doping amount 4.2 at.%, pyridine nitrogen + graphitic nitrogen total proportion 78.3%; sulfur doping amount 3.8 at.%, thiophene sulfur proportion 85.1%, oxidized sulfur proportion 14.9%; amino grafting amount 1.9 at.

[0031] High salt adsorption performance: Simulated coal chemical evaporation mother liquor system, total salt 22wt%, NaCl and It accounts for 90% of the total salt, and the system contains fluoride ions, potassium ions, calcium ions, magnesium ions, phosphate, iron, and aluminum impurities; the pollutants are a mixed system of toluene, chlorobenzene, thiophene, biphenyl, nonionic surfactants, and humic substances; the saturated adsorption capacity of the mixed organic matter is 53.4 mg-TOC / g; after 15 cycles of regeneration, the adsorption capacity retention rate is 95.9%.

[0032] Example 3: A method for preparing a high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material, comprising the following steps: (1) Preparation of ordered mesoporous-microporous hierarchical porous carbon matrix by soft template method: Weigh each raw material according to the mass ratio of F127:resorcinol:37% formaldehyde solution:ethanol:deionized water:25%~28% ammonia water =1.0:1.4:1.8:28:12:0.4; completely dissolve F127 in the ethanol-water mixed solvent, add ammonia water and stir evenly, add resorcinol and dissolve fully, then slowly add formaldehyde solution dropwise, stir at room temperature for 40 min; spread the mixture on a petri dish, allow solvent to evaporate at 45℃ for self-assembly for 18 h, and cure at 105℃ for 12 h to obtain the resin precursor; place the precursor in a tube furnace, hold at 600℃ in a nitrogen atmosphere for 2 h for carbonization to remove the template, and allow to cool naturally to obtain an ordered mesoporous-microporous hierarchical porous carbon matrix; (2) N-S dual heteroatom co-doping modification: Take 1g of the above ordered mesoporous-microporous carbon and 4g of thiourea, grind and mix thoroughly, calcine in a tube furnace at 900℃ for 2h under nitrogen atmosphere, heating rate 10℃ / min, and naturally cool to obtain N-S co-doped ordered mesoporous-microporous carbon. (3) Secondary amino covalent grafting modification: A mixed solvent of ethanol and water in a mass ratio of 5:1 was prepared, and 5% (w / w) of aminopropyltriethoxysilane was added to disperse 0.5 g of N-S co-doped carbon. The mixture was refluxed at 80 °C for 4 h. After the reaction was completed, the mixture was washed with ethanol and deionized water until neutral, and then dried at 60 °C to obtain a high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent.

[0033] Key parameters of the material prepared in this embodiment: BET specific surface area 1760 m² / g, mesopore diameter 5.2 nm, micropore diameter 0.75 nm; nitrogen doping amount 7.8 at.%, with pyridine nitrogen + graphitic nitrogen accounting for 80.1%; sulfur doping amount 6.5 at.%, with thiophene sulfur accounting for 86.4% and oxidized sulfur accounting for 13.6%; amino grafting amount 3.1 at.

[0034] High salt adsorption performance: Simulated coal chemical evaporation mother liquor system, total salt 22wt%, NaCl and It accounts for 90% of the total salt, and the system contains fluoride ions, potassium ions, calcium ions, magnesium ions, phosphate, iron, and aluminum impurities; the pollutants are a mixed system of toluene, chlorobenzene, thiophene, biphenyl, nonionic surfactants, and humic substances; the saturated adsorption capacity of the mixed organic matter is 54.8 mg-TOC / g; after 15 cycles of regeneration, the adsorption capacity retention rate is 95.1%.

[0035] Comparative Example 1: Pure N-S dual heteroatom co-doped carbon (without secondary amino modification) Only steps (1) and (2) of Example 1 were performed, omitting the amino grafting modification process. The N-S doping parameters of the material were the same as in Example 1, and there was no amino functional group modification. Performance test: Using the same simulated mother liquor system as in Example 1, the saturated adsorption capacity was 28.6 mg-TOC / g, and the capacity retention rate was 71.8% after 15 cycles of regeneration.

[0036] Comparative Example 2: Monoamino-modified carbon (without N-S framework doping) Only steps (1) and (3) of Example 1 were implemented, omitting the N-S high-temperature co-doping process. The amino grafting parameters of the material were the same as in Example 1, and there were no framework N-S active sites. Performance test: Using the same simulated mother liquor system as in Example 1, the saturated adsorption capacity was 23.9 mg-TOC / g, and the capacity retention rate was 67.5% after 15 cycles of regeneration.

[0037] Comparative Example 3: Identical Modification of Disordered Porous Carbon Ordinary disordered porous carbon was used to replace the ordered mesoporous-microporous carbon matrix of Example 1, and the remaining modification processes and parameters were completely consistent with those of Example 1. Performance testing: Using the same simulated mother liquor system as in Example 1, the saturated adsorption capacity was 30.3 mg-TOC / g, and the capacity retention rate was 64.9% after 15 cycles of regeneration.

[0038] Comparative Example 4: Commercial granular activated carbon Commercially available water-purifying grade granular activated carbon was selected without any modification treatment. Performance testing: Using the same simulated mother liquor system as in Example 1, the saturated adsorption capacity was 17.6 mg-TOC / g, and the capacity retention rate was less than 30% after 15 high-temperature regenerations.

[0039] All embodiments and comparative examples of this invention used the same test conditions: the total salt content of the simulated high-salt wastewater was 22wt%, with sodium chloride and sodium sulfate accounting for 90% of the total salt, and fluoride ions, potassium ions, calcium ions, magnesium ions, phosphate ions, iron ions, and aluminum ions were introduced as coexisting impurities; the wastewater pH was 8.2, the test temperature was 25℃, and the pressure was normal; the pollutants were a mixed organic system of toluene, chlorobenzene, thiophene, biphenyl, nonionic surfactant, and humic substances; the adsorption time was 12h, and the solid-liquid ratio was 1g:100mL; all samples were uniformly subjected to a water washing + 115℃ low-temperature thermal desorption and regeneration process.

[0040] The material structures and composition parameters prepared in all three sets of examples fall within the scope of protection of the claims. Compared with the comparative examples, the present invention achieves synergistic effects through a combination of ordered hierarchical pore structure regulation, N-S framework doping, and covalent grafting of amino groups throughout the pores. This significantly improves the adsorption capacity and cycling stability of various organic pollutants in a mother liquor system containing high salt, calcium, magnesium, fluorine, silicon, and other inorganic impurities, as well as various types of recalcitrant organic compounds.

[0041] In summary, the present invention can achieve the following effects: 1. This invention constructs a composite modification system with an ordered hierarchical porous structure, N-S framework co-doping, and secondary modification of the entire pore domain with amino groups. The system has multiple active sites that can be synergistically adapted to simultaneously and efficiently remove various types of recalcitrant organic pollutants, such as aromatics, halogenated hydrocarbons, heterocyclic aromatics, biphenyls, polychlorinated biphenyls, nonionic surfactants, humic substances, and synthetic polymers, under high-salt and high-impurity conditions. This solves the technical shortcoming of existing materials that can only adapt to a limited variety of organic pollutants.

[0042] 2. This invention employs a non-electrostatic adsorption mechanism throughout the process, completely avoiding the adsorption capacity decay caused by competitive adsorption of a large number of anions, cations, calcium, magnesium and metal ions in high-salt mother liquor and reactor residue in coal chemical, petrochemical and hydrometallurgical processes, as well as double-layer compression. It can still maintain stable adsorption performance even under harsh working conditions where the total salt content is above 20% and various inorganic impurities and complex organic matter coexist.

[0043] 3. The mesoporous-microporous interconnected multi-level pore structure designed in this invention not only reduces the mass transfer resistance of pollutants in high-salt systems and effectively alleviates the blockage of pores by the crystallization of calcium and magnesium salts, silicates, and phosphates, but also avoids the problems of humic substances, synthetic macromolecular organic matter blocking micropores, and nonionic surfactants encapsulating adsorption sites. This significantly improves the material's resistance to scaling and organic pollution, making it suitable for complex pretreatment conditions of membrane concentrates, high-salt mother liquors, and reactor residues in the chemical industry.

[0044] 4. It features a gentle regeneration process that combines water washing with low-temperature thermal desorption. Water washing can simultaneously remove salt scale debris from the pores and surfactants and macromolecular organic impurities attached to the surface. Low-temperature thermal desorption can completely preserve the carbon skeleton, N-S heteroatom active sites and amino functional groups, avoiding high-temperature ablation damage. After 15 cycles, the adsorption capacity retention rate of the material can reach more than 95%, and the cycle life is long.

[0045] 5. The preparation process parameters of this invention are precise, have good repeatability, are free of metal doping, and are green and environmentally friendly. It is easy to carry out large-scale production and can effectively solve the pain points of difficult removal of organic matter, poor salt quality, and large amount of hazardous waste in high-salt wastewater in the chemical industry. It has important engineering application value for the reduction, resource utilization, and harmless treatment of high-salt wastewater in the coal chemical, petrochemical, hydrometallurgical, pesticide, pharmaceutical, and fine chemical industries.

[0046] Furthermore, the detailed application of the high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material of this invention is as described in claims 7 to 10, and will not be repeated here. It should be noted that the aforementioned high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material achieves stable adsorption in complex high-salt systems through multiple non-electrostatic synergistic effects: pyridine nitrogen and graphitic nitrogen in the framework provide π-π stacking and halogen bond interactions, efficiently capturing large, recalcitrant organic pollutants such as aromatic hydrocarbons, heterocyclic aromatic hydrocarbons, hydrophobic halogenated hydrocarbons, biphenyls, and polychlorinated biphenyls; simultaneously, it adsorbs nonionic surfactants, humic substances, and synthetic polymeric organic compounds through hydrophobic synergistic effects; thiophene sulfur in the framework provides S-X specific affinity interactions, enhancing the adsorption stability of halogenated organic compounds; primary amino groups on the pore surface provide N-H…X hydrogen bond interactions, improving the adsorption capacity for polar organic pollutants and surfactant-type pollutants. The entire adsorption system is unaffected by the concentration of chlorine in the water. It can simultaneously remove multiple types of recalcitrant organic matter under complex high-salt conditions, and is suitable for the pretreatment of high-salt mother liquor and reactor residue with a total salt mass fraction of over 20%. It also eliminates the competitive interference of various inorganic impurities such as fluoride ions, phosphate ions, and heavy metal ions such as iron, aluminum, and manganese.

[0047] The above description is only a specific description of the invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the invention, and these improvements and modifications should also be considered within the scope of protection of the invention.

Claims

1. A high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent material, characterized in that, The adsorbent material matrix is ​​ordered mesoporous-microporous hierarchical porous carbon prepared by a soft template method; the carbon framework of the ordered mesoporous-microporous hierarchical porous carbon is in-situ co-doped with nitrogen and sulfur dual heteroatoms, and the active sites of the framework include pyridine nitrogen, graphitic nitrogen and thiophene sulfur; the outer surface and inner surface of the pores of the ordered mesoporous-microporous carbon are uniformly grafted with primary amino functional groups through silane covalent bonds. The adsorbent material uses non-electrostatic adsorption mechanisms such as π-π stacking interactions, halogen bonding, S-X affinity, and N-H…X hydrogen bonding as its core adsorption pathways, and is not affected by competition from multiple coexisting ions in high-salt systems.

2. The high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material according to claim 1, characterized in that, The ordered mesoporous-microporous hierarchical carbon has ordered mesoporous pore sizes of 2–6 nm, microporous pore sizes of 0.4–0.8 nm, and a BET specific surface area of ​​1200–1800 m² / g; the total nitrogen doping content in the carbon framework is 4.0–8.0 at.%, of which pyridine nitrogen and graphitic nitrogen account for no less than 75% of the total nitrogen content; the sulfur in the carbon framework is mainly in the form of thiophene sulfur C–S–C, and the molar percentage of oxidized sulfur species is less than 15%; the content of primary amine functional groups covalently grafted on the surface of the carbon material is 1.8–3.2 at.%.

3. A method for preparing a high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material as described in claim 1, characterized in that: The following steps are included: (1) Preparation of ordered mesoporous-microporous hierarchical carbon matrix by soft template method: F127 is used as mesoporous soft template agent, resorcinol-formaldehyde resin is used as carbon source, ethanol and deionized water mixed solvent is used as dispersion system, ammonia is used as alkaline catalyst, and ordered mesoporous-microporous hierarchical carbon matrix is ​​obtained by solvent evaporation-induced self-assembly, constant temperature curing, high temperature carbonization and template removal; (2) N-S dual heteroatom co-doping modification: The ordered mesoporous-microporous hierarchical carbon matrix prepared in step (1) is uniformly mixed and ground with thiourea solid dopant, and then pyrolyzed at high temperature under nitrogen inert atmosphere to generate pyridine nitrogen, graphitic nitrogen and thiophene sulfur active sites in situ inside the carbon skeleton to obtain N-S co-doped ordered mesoporous-microporous carbon. (3) Secondary amino covalent grafting modification: The N-S co-doped ordered mesoporous-microporous carbon obtained in step (2) is surface activated, placed in a mixed solvent system of ethanol and water, and the coupling agent aminopropyltriethoxysilane is added for liquid phase reflux reaction. Primary amino functional groups are covalently grafted on the outer surface and inner surface of the pores of the carbon material. After washing and drying, high salt resistant N-S co-doped amino modified hierarchical porous carbon adsorbent material is obtained.

4. The preparation method of the high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material according to claim 3, characterized in that: The mass ratio of each raw material in step (1) is as follows: F127: resorcinol: 37% formaldehyde solution: ethanol: deionized water: 25%~28% ammonia = 1.0: 1.0~1.4: 1.4~1.8: 22~28: 8~12: 0.2~0.4; the solvent evaporation-induced self-assembly temperature is 35~45℃, the evaporation time is 18~26h; the curing temperature is 85~105℃, the curing time is 12~20h; the carbonization temperature is 500~600℃, the heat preservation time is 2~3h, and nitrogen protection is used throughout the process.

5. The preparation method of the high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material according to claim 3, characterized in that: The mass ratio of ordered mesoporous-microporous hierarchical carbon to thiourea dopant in step (2) is 1:2 to 4; the pyrolysis calcination temperature is 700 to 900℃, the holding time is 2 to 4 hours, the heating rate is 5 to 10℃ / min, and the whole process is carried out in a nitrogen inert atmosphere.

6. The preparation method of the high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material according to claim 3, characterized in that: In step (3), the mass ratio of ethanol to water in the ethanol-water mixed solvent system is 3-5:1; the total mass fraction of aminopropyltriethoxysilane in the liquid phase system is 2%-5%; the reflux temperature is 60-80℃ and the reflux reaction time is 4-8h.

7. An application of the high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent material as described in claim 1, characterized in that: This is used to treat high-salt wastewater generated by coal chemical, petrochemical, hydrometallurgical, pesticide, pharmaceutical, and fine chemical industries. The high-salt wastewater includes membrane concentrate, evaporation crystallization mother liquor, and high-salt residue from reactors.

8. The application of the high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material according to claim 7, characterized in that: The total salt content of the high-salt wastewater is above 20%, and the main salts are sodium chloride and sodium sulfate, which together account for 80-90% of the total salt. The wastewater contains fluoride ions, potassium ions, calcium ions, magnesium ions, free silicon, carbonate ions, bicarbonate ions, nitrate ions, nitrite ions, phosphate ions, as well as iron, aluminum, manganese and heavy metal impurities.

9. The application of the high-salt-resistant N-S co-doped amino-modified hierarchical porous carbon adsorbent material according to claim 7 or 8, characterized in that: In treating the high-salt wastewater, the pH of the high-salt wastewater is controlled at 7.0 to 10.

0. The adsorbent material is used to selectively adsorb aromatic compounds, halogenated hydrocarbons, heterocyclic aromatic hydrocarbons, biphenyls, polychlorinated biphenyls, nonionic surfactants, humic substances, and synthetic polymeric recalcitrant organic pollutants in the wastewater.

10. The application of the high-salt-tolerant N-S co-doped amino-modified hierarchical porous carbon adsorbent material according to claim 9, characterized in that: After adsorption saturation, the adsorbent material is regenerated and reused. The regeneration method is as follows: first, the adsorbent material is thoroughly rinsed with deionized water, and then it is heated at 100-130℃ for 2-4 hours under normal pressure air or inert atmosphere for low-temperature thermal desorption regeneration. After cooling, it is used again for adsorption of organic pollutants in high-salt wastewater.

Citation Information

Patent Citations

  • Nitrogen-containing ordered mesopore carbon and its synthesis method

    CN100469692C

  • Nitrogen and sulfur doped porous carbon material precious metal adsorbent and preparation method thereof

    CN113893821A